Intelligent system for monitoring and forecasting the state of electrical equipment based on Microgrid - Okushko, O.; Nalyvaiko, V.; Radko, I.; Sorokin, D.; Kydryk, D. (Energy and Automation, 2025)
The concept of building an intelligent system for monitoring and forecasting the technical condition of electrical equipment within a decentralized energy system of the Microgrid type is considered. The architecture of the Predictive Maintenance (PdM) system is proposed, based on the use of sensor networks, Internet of Things (IoT) technologies, artificial intelligence (AI) and big data analytics (Big Data). A mathematical model for assessing the technical condition of electric motors is developed, which takes into account changes in the main electrical and mechanical parameters (current, voltage, temperature, vibrations, speed). The structure of the PdM process is proposed, which includes the stages of collecting, processing, analyzing data and forming predictive solutions based on machine learning algorithms. Key words: Microgrid, Predictive Maintenance, monitoring, electric motor, artificial intelligence, Internet of Things, Big Data, modeling, technical condition, energy efficiency